2018
DOI: 10.1088/1742-6596/1023/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

The Small-Angle Neutron Scattering Data Analysis of the Phospholipid Transport Nanosystem Structure

Abstract: Abstract. The small-angle neutron scattering technique (SANS) is employed for investigation of structure of the phospholipid transport nanosystem (PTNS) elaborated in the V.N.Orekhovich Institute of Biomedical Chemistry (Moscow, Russia). The SANS spectra have been measured at the YuMO small-angle spectrometer of IBR-2 reactor (Joint Institute of Nuclear Research, Dubna, Russia). Basic characteristics of polydispersed population of PTNS unilamellar vesicles (average radius of vesicles, polydispersity, thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Various approaches exist to tackle the problem of modelling and fitting small-angle scattering data from model lipid membranes (Pabst et al, 2000;Pencer & Hallett, 2000;Pé rez & Koutsioubas, 2015;Skar-Gislinge et al, 2015;Heftberger et al, 2014;Zemlyanaya et al, 2016Zemlyanaya et al, , 2018Konarev et al, 2020). In most cases, scattering length density (SLD) profiles of symmetric lipid bilayers are represented in the form of step functions (Pencer & Hallett, 2000) or Gaussians (Pabst et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches exist to tackle the problem of modelling and fitting small-angle scattering data from model lipid membranes (Pabst et al, 2000;Pencer & Hallett, 2000;Pé rez & Koutsioubas, 2015;Skar-Gislinge et al, 2015;Heftberger et al, 2014;Zemlyanaya et al, 2016Zemlyanaya et al, , 2018Konarev et al, 2020). In most cases, scattering length density (SLD) profiles of symmetric lipid bilayers are represented in the form of step functions (Pencer & Hallett, 2000) or Gaussians (Pabst et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the photo, one can see discrete particles that are predominantly spherical and/or rod-shaped. Previously, a combination of two methods-small-angle neutron scattering in the range of PhTNS concentration in heavy water of 5-25% by weight and small-angle scattering of X-ray synchrotron radiation in several concentrations in water-was used to determine the single-layer vesicular structure of phospholipid transport nanosystem (PhTNS) [23,24]. It was found that the size of vesicles decreased with an increase in the maltose concentration and was about 27.2 + 0.2 nm at a concentration of 20%.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%